Aristotle: happiness (eudaimonía) as the end of ends - Ramírez Muñoz S.J., Fabio (Estudios de Filosofía, 2002)
The purpose of this article is to deal with the theme of the ultimate end or happiness in Aristotle’s ethics, and specifically in the Nicomachean Ethics, but distinguishing it into three themes that should not be confused: the end of politics as an architectural discipline, the end of good human life and happiness. Although these two ends and happiness, according to Aristotle, are the same, it could be said, using a very his expression, that "its essence is not the same." The separate treatment of these aspects can clarify more than one confusion or obscurity, and their articulation, once distinguished, allows ordering the main general themes of Aristotelian ethics.